Carbon nanotubes interaction with amorphous and semi‐crystalline domains of polypropylene in melt‐mixed composites: Influence of multiwall carbon nanotubes agglomerate and their modifications. (26th June 2021) - Banerjee, Joyita; Samajdar, Rajarshi; Kummara, Sreenivas; Panwar, Ajay S.; Mukhopadhyay, Kingsuk; Saxena, Arvind K.; Bhattacharyya, Arup R.
Abstract: Polypropylene (PP) and multi‐walled carbon nanotubes (MWCNTs) composites were prepared by melt‐mixing with two types of MWCNTs of varying agglomerate size. Agglomerate dominated dispersion was observed in the PP matrix, wherein N‐MWCNTs exhibit a finer dispersion as compared to D‐MWCNTs. Further, MWCNTs were encapsulated by Li‐salt of 6‐amino caproic acid in various proportions along with PP‐g‐maleic anhydride in order to achieve finer MWCNTs dispersion. Thermogravimetric analysis exhibited an increase in onset of degradation temperature and higher residual weight (%) at 500 °C of PP with increased MWCNTs concentration, which suggests the formation of a thicker "interphase." Glass transition temperature of the PP phase was increased monotonically as a function of unmodified MWCNTs concentration, which suggests a strong interfacial interaction between PP and MWCNTs. An extensive analysis was carried out with modified MWCNTs based PP composites. Moreover, MWCNTs act as a strong hetero‐nucleating agent manifesting in smaller spherulite size of PP, wherein bulk crystallization temperature is increased to 130 °C of the PP phase at 5 wt% MWCNTs content. The influence of unmodified and modified MWCNTs on the interaction between the PP chains and MWCNTs in the amorphous phase as well as in the crystalline domains are analyzed in PP/MWCNTs composites. Abstract :